2015
DOI: 10.1089/neu.2014.3449
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Brain Stimulation for Persistent Postconcussion Symptoms in Mild Traumatic Brain Injury

Abstract: Mild traumatic brain injury (mTBI) is typically followed by various postconcussive symptoms (PCS), including headache, depression, and cognitive deficits. In 15-25% of cases, PCS persists beyond the usual 3-month recovery period, interfering with activities of daily living and responding poorly to pharmacotherapy. We tested the safety, tolerability, and efficacy of repetitive transcranial magnetic stimulation (rTMS) over the left dorsolateral prefrontal cortex (DLPFC) for alleviating PCS. Fifteen eligible pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 38 publications
2
92
0
1
Order By: Relevance
“…Thus, Koski et al 25 have hypothesised that rTMS over the DLPFC, which is an effective treatment for symptoms of major depressive disorder, may have utility in alleviating PPCS. In a study using a near-identical treatment protocol to the one described in this case, Koski et al showed a significant reduction in PPCS following 20 rTMS sessions in patients with mTBI with symptoms persisting for greater than 3 months 25…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Koski et al 25 have hypothesised that rTMS over the DLPFC, which is an effective treatment for symptoms of major depressive disorder, may have utility in alleviating PPCS. In a study using a near-identical treatment protocol to the one described in this case, Koski et al showed a significant reduction in PPCS following 20 rTMS sessions in patients with mTBI with symptoms persisting for greater than 3 months 25…”
Section: Discussionmentioning
confidence: 99%
“…52 Cortical activity induced by left prefrontal cortex anodal transcranial direct-current stimulation in patients with TBI correlated with improvements on neuropsychological tests.…”
Section: Neocortical Regionsmentioning
confidence: 97%
“…In a single uncontrolled small study, 4-week treatments with rTMS showed mild improvement in PCS but no change in cognitive function [174]. The exact mechanisms behind rTMS-induced plasticity are still unknown.…”
Section: Repetitive Transcranial Magnetic Stimulation (Rtms)mentioning
confidence: 99%